Prehranjevanje in pitje med porodom - Skoberne, Mihaela (Obzornik zdravstvene nege, 2003)
Most of the existing nursing proceedings regarding nutritional needs of women in labour - which in most cases consist of planned abstinence from food and drink with the aim of preventing regurgitation of stomach contents and its inhalation (Mendelson's syndrome, which is, however, very rare). To many women, abstinence from food does not present a problem, but for some, such an imposed hunger during the first labour period can be a traumatic experience. The article brings some findings which can contribute to better understanding and more audacious search for alternatives in the frames of the existing practice and can direct us in informing women about consumption of food and drink in labour.
Keywords: childbirth; Drinking; Eating; Energetska presnova; Energy Metabolism; Gastric Emptying; Gastroesophageal Reflux; Gastroezofagealni refluks; Hranjenje; human pregnancy; Labor; Nosečnost; Pitje; Pljučnica aspiracijska; Pneumonia, Aspiration; Porod; Pregnancy; Želodec, praznjenje